Modeling and nonlinear parameter identification for hydraulic servo-systems with switching properties. (August 2019) - Maier, Clemens C.; Schröders, Simon; Ebner, Wolfgang; Köster, Marius; Fidlin, Alexander; Hametner, Christoph
Highlights: Physical modeling of a hydraulically actuated clutch in automatic transmissions or dedicated hybrid transmissions, which features an electric pump drive but no hydraulic accumulator. Derivation of simplified hydraulic models by topology reduction and analytical simplification of system dynamics. Model validation using real testbed measurements. Model-based design of experiments. Destruction free parameter identification of hydraulic servo-systems using particle swarm optimization (PSO) and real testbed measurements. Abstract: Today's automotive industry faces challenges in reducing emissions to comply with ever tightening statutory provisions. The future is set to provide cleaner vehicles which, on the one hand, reduce the required energy consumption while on the other hand are fit to fulfill customer preferences with regard to driving performance. As a result, the design and control of automotive components in the drive train are reconsidered. This paper treats the modeling and parameter identification of a hydraulic circuit for clutch actuation in automatic transmissions (AT) or dedicated hybrid transmissions (DHT). The examined hydraulic servo-system's function is to provide the necessary pressure and volume flow for clutch actuation without usage of a hydraulic accumulator. Physical modeling and parameter identification is executed using testbed measurements of an according prototype hardware, aiming to contribute in finding a way towards destruction free identification of hydraulic systems. The nonlinear identification for the examined system that shows switching behaviour is performed using the derivation free particle swarm optimization (PSO) method. The physical models are developed for the purpose of being employed for the design of a trajectory tracking nonlinear model-based control scheme for clutch actuation based on the concept of input-output linearization.